2016
DOI: 10.1016/j.jce.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Workplace democracy and job flows

Abstract: This paper investigates the relationship between workplace democracy and job flows by comparing the behavior of worker-managed firms (WMFs) and conventional firms (CFs). The empirical analysis relies on high frequency administrative firm-level panel data from Uruguay over the period April 1996-July 2009. The main findings of the paper are that (1) WMFs exhibit much more stable job dynamics than CFs; (2) both types of firms have decreasing in age and increasing in size gross job creation profiles; (3) there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Since 1990 and specifically after 2003, Academy of Management Annual Meeting conference “Democracy in a Knowledge Economy” and with the August 2004 special topic issue of the Academy of Management Executive “Democracy in and Around Organizations,” this political and western‐based phenomenon received considerable attention from researchers around the world. Nonetheless, in this tenor, literature evidenced that implementing democratic practices at work will promote a number of organizational and employee related outcomes in a positive way including trust and communication (Holtzhausen, , ), job flows (Alves, Burdin, & Dean, ), improved psychological capital (Geckil, Ileri, & Kaya, ), organization citizenship (Geckil & Tikici, ), equality (Oseen, ), higher job satisfaction and commitment (Unterrainer, Weber, & Palgi, ; Vitols, ; Weber, Unterrainer, & Schmid, ), employee well‐being (Vliet, ), socio‐moral climate (Weber et al, ) improved employee health (Foley & Polanyi, ), freedom (Fenton, ), better labor relations (Hickland, ), enhanced productivity and creativity (Deetz, ; Harrison & Freeman, ; Kerr, ), employee voice (Dahl, ), and reduction in violence (Karstedt, ), decreasing the turnover rate (Heller, ; Strauss, 2006); improving work relationships (Gunn, ); decreasing job stress (Franca & Pahor, ; Kalleberg, Nesheim, & Olsen, ); improving the skills and abilities of individuals toward more collaboration (Verdorfer, Weber, & Unterrainer, ). Although there exists a number of studies supporting democratic models for organizations and its related outcomes; yet there are faint whispers for the paradigm of organizational democracy among contemporary scholars in the social and management discourse.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1990 and specifically after 2003, Academy of Management Annual Meeting conference “Democracy in a Knowledge Economy” and with the August 2004 special topic issue of the Academy of Management Executive “Democracy in and Around Organizations,” this political and western‐based phenomenon received considerable attention from researchers around the world. Nonetheless, in this tenor, literature evidenced that implementing democratic practices at work will promote a number of organizational and employee related outcomes in a positive way including trust and communication (Holtzhausen, , ), job flows (Alves, Burdin, & Dean, ), improved psychological capital (Geckil, Ileri, & Kaya, ), organization citizenship (Geckil & Tikici, ), equality (Oseen, ), higher job satisfaction and commitment (Unterrainer, Weber, & Palgi, ; Vitols, ; Weber, Unterrainer, & Schmid, ), employee well‐being (Vliet, ), socio‐moral climate (Weber et al, ) improved employee health (Foley & Polanyi, ), freedom (Fenton, ), better labor relations (Hickland, ), enhanced productivity and creativity (Deetz, ; Harrison & Freeman, ; Kerr, ), employee voice (Dahl, ), and reduction in violence (Karstedt, ), decreasing the turnover rate (Heller, ; Strauss, 2006); improving work relationships (Gunn, ); decreasing job stress (Franca & Pahor, ; Kalleberg, Nesheim, & Olsen, ); improving the skills and abilities of individuals toward more collaboration (Verdorfer, Weber, & Unterrainer, ). Although there exists a number of studies supporting democratic models for organizations and its related outcomes; yet there are faint whispers for the paradigm of organizational democracy among contemporary scholars in the social and management discourse.…”
Section: Introductionmentioning
confidence: 99%
“…, Alves et al. ). In addition, it has also been shown that despite cooperatives having more egalitarian compensation structures, they suffer from brain drain (high‐ability members are more likely to quit) (Burdín ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…, Alves et al. ), and into the encouragement of the participation of their workers and members, thereby bringing about an increase in their job satisfaction (Rothschild‐Whitt and Whitt , Miller and Monge , Avey et al. ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations